Esperienze pionieristiche di film making scolastico al Villaggio di Corea (Livorno, 1976-'77). Storie, verifiche, riflessioni - Felini, Damiano (Studi sulla Formazione/Open Journal of Education, 2019)
In the 1960s and 1970s, the experiences of educational film making represented an attempt to bring into the school context unusual activities that successfully tried to achieve goals of media literacy, social growth in an emancipatory perspective, and a connection between the classroom and external environments. After a brief overview on the Italian experiences, the article reconstructs and interprets the significant case of the educational film making in the Corea School Village, Livorno, and highlights some of its noticeable features: the strong social ideals, the attention to the “conscientization” of the pupils, the learning-by-doing methodology, the continuity between the different sections of the Village, the Action-Research approach, and the high quality documentation of the experiences